Molecular Ultrasound Monitoring of Early Artery Injury After Carotid Balloon Angioplasty - Mo, Xinhai; Yan, Fei; Zhang, Bo (Frontiers in Pharmacology, 2019)
Cardiovascular intervention is a common treatment procedure for many cardiovascular diseases. But restenosis often occurs after these procedures, greatly discounting their long-term therapeutic effects. Early detection of endothelial denudation is helpful for the diagnosis and prevention of restenosis. Here, we fabricated targeted microbubbles by conjugating anti-collagen IV antibodies to the surface of biotinylated microbubbles (MBColIV) and applied them for ultrasound molecular imaging of endothelial injury at early stage. Our results showed that the MBColIV, with a typical multi-peak particle distribution, was successfully constructed, which was confirmed by Alexa Fluor® 555-labeled secondary antibody. Ex vivo adhesion of microbubbles revealed that MBColIV can effectively and specially bind to the surface of balloon-injured carotid artery. The in vivo animal experiments showed ultrasound molecular imaging signals from carotid artery-injured rats administrated with MBColIV were significantly higher than those administrated with isotype control microbubbles. Histological staining of the left carotid common artery revealed that collagen IV was obviously exposed after endothelium denudation in balloon-injured artery. In conclusion, our current study provides an effective approach to detect vascular injury at the early stage and a potential platform for image-guided therapy to vascular injury.